Respuesta :

Answer:

[tex]g(x)=3\cdot3^x-2[/tex]

Step-by-step explanation:

The base function is [tex]f(x)=3^x[/tex] .

The transformed graph now has a horizontal asymptote of y=-2.

So the transformed equation is of the form [tex]g(x)=a(3^x)-2[/tex]

We now have to determine the value of [tex]a[/tex]

[tex]g(0)=1[/tex]

[tex]-1=a*3^{-1}-2[/tex]

[tex]1=a*3^{-1}[/tex]

[tex]a=3[/tex]

Therefore the equation is [tex]g(x)=3\cdot3^x-2[/tex]

Answer:

I took the test on k12. Hope this helps :)

Step-by-step explanation:

Ver imagen blazetoxic123